MOLECULAR DETECTION AND ANALYSIS OF MUT L GENE FROM Pseudomonas aeruginosa IN URINARY TRACT INFECTION PATIENTS - Hamzah, A. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was aimed to detect and analysis of mutL gene from Pseudomonas aeruginosa in UTI patients .Two hundred midstream urine specimens were collected from UTI patients. Laboratory diagnosis carried out depend on morphological and biochemical tests and confirmed by using VITEK- 2 Compact system. The results showed twenty isolates of Pseudomonas aeruginosa from two hundred urine specimens in percentage (10%). Genome extracted from all twenty isolates by specific kit , then amplification of mutL gene in PCR by specific primers. Sequencing process of product PCR of all twenty isolates was done. MutL gene sequencing of all twenty isolates was alignment in NCBI and the phylogenetic tree was drew by using Geneious 10 software among sequence of locally isolates. The results of analysis sequence of mutL gene from locally isolates in phylogenetic tree showed seven different groups. Analysis comparison sequencing of mutL gene between locally and global isolates showed eight different groups in phylogenetic tree included three groups (A,G,H) identical with global isolates and five groups (B,C,D,E,F) were not identical with global isolates , therefore selected one isolate (SD-9) from these five locally groups and documented as anew Iraqi isolate in national GenBank and accepted under accession number (LOCUS MF898429) of nucleotides sequence and protein ID(AUI39222.1).